REGENERATION OF FREE CYANIDE BY SELECTIVE OXIDATION OF THIOCYANATES - Shonazarova Shahnoza Isakulovna (PEDAGOGS, 2024)
The invention can be used in the mining industry, the gold mining industry and at non-ferrous metallurgy enterprises for the recovery of free cyanide from waters and pulps containing thiocyanates, as well as for their purification from these compounds. The method includes oxidative treatment of waters or pulps at pH less than 6.0, stripping and trapping of hydrocyanic acid from exhaust gases in an alkaline absorber, alkalization of waters or pulps after their oxidative treatment. Part of the water or pulp after oxidative treatment or stripping of hydrocyanic acid is sent for mixing with the original feed in such a ratio that the pH of the mixture is at the level of 1.5-2.5. Waters or slurries can be treated simultaneously with the recovery of free cyanide to any given depth, and in addition to thiocyanates, cyanides can also be present. Processing is carried out both in periodic and continuous modes, hydrocyanic acid from the exhaust gases is captured by alkaline waters or pulps. The method provides a reduction in the consumption of reagents during the regeneration of free cyanide while maintaining a high degree of their recovery.